(untitled) (Bangladesh Journal of Child Health, 2022)
Sweet syndrome (SS) is a rare dermatosis of unknown etiology. It is characterized by fever, neutrophilia, raised and painful plaques on the skin of the face, neck, limbs, and histologically by dermal infiltration of neutrophils. Here, we present a ten-year-old boy who presented with fever and multiple skin lesions for 15 days. On examination, he was febrile and presented with multiple nodular, tender, erythematous rash on face and limbs. Laboratory findings revealed raised inflammatory markers with neutrophilic leukocytosis, skin biopsy showed hyperkeratosis and neutrophilic infiltration of the dermis. Typical history, laboratory investigations including skin biopsy findings were suggestive of diagnosis of SS. Prolonged fever and characteristics skin lesions in any child should be suspected for this rare syndrome. It should be kept in mind as a differential diagnosis in the day-today clinical practice for effective management of this rare disease. BANGLADESH J CHILD HEALTH 2021; VOL 45 (3) : 172-174